2007
DOI: 10.1016/j.neuropharm.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic tolerance to microinjection of the μ-opioid agonist DAMGO into the ventrolateral periaqueductal gray

Abstract: Repeated administration of the relatively low-efficacy micro-opioid receptor agonist morphine induces tolerance to its antinociceptive effects. High-efficacy agonists such as D-Ala2NMePhe4,Gly-ol5 (DAMGO) have been shown to be less effective at producing tolerance, suggesting that different neural mechanisms underlie tolerance to these agonists. However, the correlation between agonist efficacy and tolerance development has not been examined within the ventrolateral periaqueductal gray (vPAG), a brain area kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
0
27
1
Order By: Relevance
“…The tolerance liability of an opioid agonist is believed to be inversely related to its ability to internalize the MOP-opioid receptor [33] ; low-efficacy agonists, such as morphine, are poor internalizing agents, while DAMGO and other high-efficacy MOP agonists result in substantial receptor internalization. In contrast, this study and others [12,34] have found that pronounced tolerance occurs following repeated administration of DAMGO into the vlPAG.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The tolerance liability of an opioid agonist is believed to be inversely related to its ability to internalize the MOP-opioid receptor [33] ; low-efficacy agonists, such as morphine, are poor internalizing agents, while DAMGO and other high-efficacy MOP agonists result in substantial receptor internalization. In contrast, this study and others [12,34] have found that pronounced tolerance occurs following repeated administration of DAMGO into the vlPAG.…”
Section: Discussioncontrasting
confidence: 94%
“…These results indicate that similar mechanisms likely underlie tolerance to morphine and DAMGO within the PAG [12] .…”
mentioning
confidence: 57%
“…Nociception was assessed using the hot-plate test 15 min after each injection. This procedure has been shown to produce reliable dose-response curves (Morgan et al, , 2006Meyer et al, 2007).…”
Section: Microinjectionsmentioning
confidence: 99%
“…The PAG is a mediator of opioid analgesia 43, 54, 78 , and MORs are expressed by vlPAG-RVM projection neurons 59 . As nAChR s and MORs have opposing effects on excitability, we hypothesized non-overlapping distribution of these receptors among vlPAG projection neurons.…”
Section: Resultsmentioning
confidence: 99%
“…PNU-120596 and PHA-543613 concentrations were determined empirically in pilot testing, as this is the first study conducting intra-vlPAG injections of these drugs. DAMGO dose and pretreatment times were based upon Meyer et al 54 . In the α7 antagonist + PHA-543613 studies, MLA (90 pmol) or αBGT (1.5 pmol), were focally administered into the vlPAG 10 or 30 min prior to formalin injection, respectively, to allow for diffusion and binding to the receptors.…”
Section: Methodsmentioning
confidence: 99%